Learning organizations: Prerequisite for successful tourism organizations - Natasa Kraleva (UTMS Journal of Economics, 2011)
Nowadays, each and every organization, including the tourism organizations should be learning organizations. The globalization and the competition affect the process of working of tourism organizations, where only the organizations which have knowledge, and are learning organizations can succeed. In a time of constant change, tourism organizations can have a competitive advantage only if they can do something or offer something different than their competitors. Many organizations in order to enable the learning process, should firstly undertake changes in the organization design, the organizational culture and the leadership style. The paper discusses the relevance of implementing the process of learning organizations as a concept for successful tourism organizations.
Keywords: 330; learning organizations; tourism organizations; knowledge; advantage